THE EFFECT OF WORKLOADS ON TURNOVER INTENTION WITH WORK STRESS AS MEDIATION AND SOCIAL SUPPORT AS MODERATED VARIABLES - Wibowo, Akbar; Setiawan, Margono; Yuniarinto, Agung (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study was to examine and analyze the relationship of workload, work stress, and social support for employee turnover intentions of PT. Bentoel Prima Malang. This study uses a population of all Primary Manufacturing Department (PMD) permanent employees of 83 employees. All members of the population are used as research samples (total sampling). Analysis tool to test the relationship between variables using the help of smartPLS 3.0. The results showed that workload did not significantly influence turnover intention. Job stress plays a mediating role between workload and work stress. Social support does not moderate work stress on turnover intention. The theoretical implications of this research provide opportunities for further research on workloads, not a major factor in employee decisions leaving the organization. Practical implications in this study provide new insights to companies and employees about the negative impact of increasing workload.